2009
DOI: 10.1007/s00248-009-9600-2
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid-Containing Lipopolysaccharides of Salmonella O48 Strains—Potential Role in Camouflage and Susceptibility to the Bactericidal Effect of Normal Human Serum

Abstract: Sialic acid (N-acetylneuraminic acid, NeuAc) plays an essential role in protecting gram-negative bacteria against the bactericidal activity of serum and may contribute to the pathogenicity of bacteria by mimicking epitopes that resemble host tissue components (molecular mimicry). The role of sialic acid (NeuAc)-containing lipopolysaccharides (LPS) of Salmonella O48 strains in the complement activation of normal human serum (NHS) was investigated. NeuAc-containing lipooligosaccharides cause a downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Long-term investigations carried out on Salmonella O48 shown that strains differ in the susceptibility to various sera, human or animal , 2010a, 2010b, 2009b, 2009cFutoma et al 2005). These authors suggest that the presense of sialylated LPSs do not play a decisive role in determining bacterial resistance to the bactericidal activity of serum, and that the presence of NeuAc in the LPS structure is not sufficient to block activation of the alternative pathway of complement in serum.…”
Section: Susceptibility Of Salmonella Spp To the Bactericidal Activimentioning
confidence: 99%
See 3 more Smart Citations
“…Long-term investigations carried out on Salmonella O48 shown that strains differ in the susceptibility to various sera, human or animal , 2010a, 2010b, 2009b, 2009cFutoma et al 2005). These authors suggest that the presense of sialylated LPSs do not play a decisive role in determining bacterial resistance to the bactericidal activity of serum, and that the presence of NeuAc in the LPS structure is not sufficient to block activation of the alternative pathway of complement in serum.…”
Section: Susceptibility Of Salmonella Spp To the Bactericidal Activimentioning
confidence: 99%
“…The above-mentioned authors , 2010a, 2010b, 2009b, 2009cFutoma et al 2005) and Sarowska and co-workers (2010) described the results of Salmonella susceptibility to human and bovine serum. Bactericidal activity of serum was determined as described previously (Doroszkiewicz, 1997).…”
Section: Susceptibility Of Salmonella Spp To the Bactericidal Activimentioning
confidence: 99%
See 2 more Smart Citations
“…The numbers of CFU/mL from the bactericidal assays were converted to percentage survival values, where the starting inoculum at T 0 was set at 100%, and values for the survival rates were expressed as log10% CFU/mL (Bugla-Płoskońska et al 2010b, Skorek et al 2013. The data from each assay were compared by the analysis of ANOVA/MANOVA.…”
Section: Statistical Analysesmentioning
confidence: 99%